The adaptability and resilience of Indonesian EFL teachers during emergency online education - Suwartono, Tono; Nurhayati, Sri; Mustari, Mohamad; Erlawati, Erlawati (Edelweiss Applied Science and Technology, 2025)
The COVID-19 pandemic has radically transformed the teaching and learning process from in-class instruction to remote learning. This changing situation leads to barriers for EFL teachers in executing their teaching plans. Therefore, they should be able to deal with such challenges for instructional continuity. This study aimed to investigate the challenges that EFL teachers face, examine their adaptability to the conditions, and explore their strategies in implementing online education. Seven junior high school EFL teachers were purposefully recruited from public and private schools in a town in southwestern Central Java, Indonesia, to participate in this study. The data were elicited through interviews and analyzed using qualitative thematic analysis techniques. The study revealed that the challenges encountered by the EFL teachers were mainly internet connectivity issues, low classroom participation among students, poor motivation in task completion, unsupported devices, and limited infrastructure support. In response to these challenges, the EFL teachers modified their lesson plans, improved their competencies, and adapted the material. Furthermore, in dealing with the challenges, the teachers made special efforts: selecting a simple online learning platform, monitoring students’ learning processes, contextualizing the material to daily life, providing intensive feedback, and collaborating with students’ parents. Recommendations for classroom practices, policymakers, and future research directly related to the findings of the current study are provided.